Relevance of the location of lesions in the glenoid labrum during its diagnosis and clinical approach. Literature review. - Osorio-Roa, Diana Marcela (2022)
The glenoid labrum is a structure composed of fibrocartilaginous tissue, it has a fundamental function in the shoulder such as serving as insertion of glenohumeral ligaments and fascicles of the articular capsule which gives stability to the joint; frequently multiple affections are observed that can limit its correct functionality. The different lesions have been classified by different authors according to the site where they occur, many of them requiring a detailed physical examination where a variety of techniques are implemented, but being really the imaging diagnosis through conventional magnetic resonance imaging or arthroscopy the one that specifies the type of lesion. Different methods have been proposed for the approach, ranging from non-surgical to those that require open procedures or arthroscopy, depending on the presentation of the lesion.